Calculation and measurements of self-ignition nuclei in diesel combustion - Marcic, Milan; Avsec, Jurij; Wensing, Michael; Schmid, Marcus; Leipertz, Alfred; Fettes, Christian (Energy & Fuels, 2010)
This paper describes a computer simulation of diesel spray formation and the locations of self-ignition nuclei. The spray is divided into small elementary volumes, in which the amounts of fuel, fuel vapors, and air and mean, maximum, and minimum fuel droplet diameters are calculated, as well as their number. The total air/fuel and air/fuel-vapor ratios are calculated for each elementary volume. The paper introduces a new criterion for determining self-ignition nuclei based on assumptions that the strongest self-ignition probability lies in those elementary volumes containing the stoichiometric air ratio, where the fuel is evaporated or the fuel droplet diameter is equal to or lower than 0.0065mm. The most efficient combustionwith regard to consumption and emissionwill be in those elementary volumes containing the stoichiometric air ratio and fuel droplets with the lowestmean diameters.Measurements of injection and combustionwere carried out in a transparent research engine. This engine is a single-cylinder transparent engine based on the Audi V6 engine, equipped with a Bosch common rail injection system. The optical part of the experimental setup contains two different lasers, while the camera system allows for simultaneously detecting four signals: the Mie scattering of the injected fuel, the laser-induced fluorescence (LIF) of fuel and vapor, light emissions from the flame indicating the premixed combustion mode, and flame emissions indicating the diffusion mode. A comparison of the computed points to the highest self-ignition probability and the measured points where self-ignition occurred showed good matching. Copyrigh © 2009 American Chemical Society.
Created from Fastlane, Scopus look-up